2014
DOI: 10.1186/1471-2407-14-689
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Jacarelhyperol A induced apoptosis in leukaemia cancer cell through inhibition the activity of Bcl-2 proteins

Abstract: BackgroundHypericum japonicum Thunb. ex Murray is widely used as an herbal medicine for the treatment of hepatitis and tumours in China. However, the molecular mechanisms of its effects are unclear. Our previous research showed that extracts of H. japonicum can induce apoptosis in leukaemia cells. We also previously systematically analysed and isolated the chemical composition of H. japonicum.MethodsThe fluorescence polarisation experiment was used to screen for inhibitors of Bcl-2 proteins which are proved as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The investigated compounds, including JapA, were obtained from a natural product library established in Dr. Wei-Dong Zhang's laboratory, with their purity being >95% (confirmed by IR, ESI-MS, NMR, and HPLC/MS n ) [ 48 ]. All chemicals and solvents were of the highest analytical grade available.…”
Section: Methodsmentioning
confidence: 99%
“…The investigated compounds, including JapA, were obtained from a natural product library established in Dr. Wei-Dong Zhang's laboratory, with their purity being >95% (confirmed by IR, ESI-MS, NMR, and HPLC/MS n ) [ 48 ]. All chemicals and solvents were of the highest analytical grade available.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on this plant have revealed the presence of flavonoids, xanthonoids, chromone glycosides, phloroglucinol derivatives and lactones, and many of these secondary metabolites exhibit versatile pharmacological activities34567.…”
mentioning
confidence: 99%
“…Hypericum japonicum Thunb, an annual herbaceous plant of the genus Hypericum (Hypericaceae), widely distributed in Asia, Oceania, and North America, has been historically used for the treatment of hepatitis, tumors, and gastrointestinal disorder in Chinese traditional medicine 1 2 . Previous studies on this plant have revealed the presence of flavonoids, xanthonoids, chromone glycosides, phloroglucinol derivatives and lactones, and many of these secondary metabolites exhibit versatile pharmacological activities 3 4 5 6 7 .…”
mentioning
confidence: 99%
“…The docking method that was used is described in previous work. [4] In summary, molecular modeling was performed using Maestro 9.0. The crystal structure of an MDM2/nutlin-3a complex with a resolution of 1.6 Å (PDB code: 4HG7) was downloaded from the Protein Data Bank (PDB, http://www.pdb.org) and was prepared with the 'Protein Preparation Wizard' workflow with the default settings.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…[2] Thus, PPIs are attractive molecular targets for novel therapies. [3,4] The MDM2-p53 interaction is a good example of signaling proteins for which PPIs have been targeted and small-molecule inhibitors have entered clinical trials. [5] The p53 tumor suppressor protein is a transcription factor that is responsible for maintaining genome integrity, which is related to several cellular processes, including the cell cycle, apoptosis, DNA repair, and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%